Online Monitoring of a Sequencing Batch Reactor Treating Domestic Wastewater. (2017) - Alattabi, Ali Waheid; Harris, Clare; Alkhaddar, Rafid; Alzeyadi, Ali; Abdulredha, Muhammad
Abstract: Domestic wastewater consists of considerable concentrations of pollutants that can boost water eutrophication if not treated before final discharge, which could damage the ecosystem and negatively affect human health. Sequencing batch reactor (SBR) technology is considered a promising biological wastewater treatment technology to address these issues. In recent years, SBR selection has increased as an effective technology for the treatment of domestic and industrial wastewaters due to its setup simplicity and ease of operation. However, many researchers have reported differences in cycle time. The importance and originality of this study is that it explores the parameters of pH, temperature, oxidation-reduction potential (ORP) and dissolved oxygen (DO) throughout the SBR cycle to predict the end of the treatment cycle. A laboratory-scale SBR was used in this study with a five-litre working volume. It was equipped with four electronic sensors (probes) to monitor the pH, ORP, temperature and DO. The SBR was operated under constant aeration, 1.0 l/min, ±12 C° temperature and 6 h cycle time. Each cycle of the SBR operation included Fill (30 minutes), React (240 minutes), Settle (30 minutes), Draw (30 minutes) and Idle (30 minutes). Influent and effluent samples were analysed for COD, ammonia-N and nitrate-N. The pH, ORP and DO values at the end of the 6 h HRT treatment cycle were between 6.6-7.9, 147-169 mV and 4.6-6.6 mg/l respectively. The results show complete degradation of COD and nitrogen compounds was seen when the DO profile increased due to bacterial respiration. The results prove that online monitoring of SBR operating parameters could significantly predict the end of the treatment cycle, and the pH, DO and ORP profiles could be used as onsite process control parameters.